A new species of Microvelia Westwood, 1834 (Hemiptera: Heteroptera: Veliidae) from southeastern Brazil - Magalhães, Oséias Martins; Machado, Gustavo Lisboa Vieira; Carneiro, Marco Antonio Alves; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2021)
Microvelia joceliae Magalhães & Moreira, sp. nov. is described and illustrated based on material from Parque Natural Municipal das Andorinhas, Minas Gerais State, in southeastern Brazil. The new species can be distinguished from congeners occurring in the region by the pronotum of the apterous form covering almost the entire thorax dorsally, proepisternum with black denticles, male abdominal segments V–VII ventrally depressed, shape of the asymmetrical parameres, and female abdominal laterotergites reflected over the mediotergites and almost touching over segments V–VII.